PENGARUH STRUKTUR MODAL DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN (Studi pada Sektor Real Estate dan Property yang Terdaftar di Bursa efek Indonesia periode Tahun 2011-2013) - Jayanthi, Ni Made Dwi; Saraswati, Erwin (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to examine at the effect of capital structure and Corporate Social Responsibility (CSR) on firm value to improve firm value itself. This research uses purposive sampling methods in order to get the apropriate samples. This method produces 133 real estate and property companies which are listed in Indonesian Stock Exchange (IDX) during the year 2011 to 2013. Analytical  methods  that  is  used  in  this  research  is  descriptive  statistics  and multiple linier regression. The result of this study shows that capital structure improves firm value, but CSR doesn’t. Keywords: capital structure, Corporate Social Responsibility (CSR), firm value